Pyridinic Nanographenes by Novel Precursor Design - Reger, David; Schöll, Kilian; Hampel, Frank; Maid, Harald; Jux, Norbert (Chemistry - A European Journal, 2021)
In this work we present the solution-synthesis of pyridine analogues to hexa-peri-hexabenzocoronene (HBC)-which might be called superpyridines-via a novel precursor design. The key step in our strategy was the pre-formation of the C-C bonds between the 3/3' positions of the pyridine and the adjacent phenyl rings-bonds that are otherwise unreactive and difficult to close under Scholl-conditions. Apart from the synthesis of the parent compound we show that classical pyridine chemistry, namely oxidation, N-alkylation and metal-coordination is applicable to the pi-extended analogue. Furthermore, we present basic physical chemical characterizations of the newly synthesized molecules. With this novel synthetic strategy, we hope to unlock the pyridine chemistry of nanographenes.
CRIS-Team WoS Importer:2021-01-29